EVALUATION OF THE IMPLEMENTATION OF THE ISPA CONTROL PROGRAM IN THE MANAGEMENT OF TODDLER PNEUMONIA AT THE PUTRI AYU PUBLIC HEALTH CENTER IN JAMBI CITY - Regina Cahyani; Arnild Augina Mekarisce; Adila Solida; Rumita Ena Sari (PT. Radja Intercontinental Publishing, 2026)
Acute respiratory infections including pneumonia remain a major cause of morbidity and mortality in children under five and case detection in primary care is often low despite the availability of guidelines; Putri Ayu Community Health Center recorded 53 cases of pneumonia in children under five in 2025 with a detection coverage of 26.49% of the target of 90%, so an implementation evaluation is needed. Objective: To evaluate the implementation of the ARI Control Program in the management of pneumonia in children under five using a logic model (input → activity → output). Method: Descriptive qualitative case study at Putri Ayu Community Health Center (Dec 2024–Apr 2026) with snowball sampling (n=9 informants: manager, clinician, pharmacist, emergency department, nutritionist, and caregiver); data collection through in-depth interviews, participant observation, and document review; thematic analysis using NVivo 12 and the Miles-Huberman framework with triangulation. Results: Input was partially adequate but training was uneven and there was a shortage of nurses during peak periods; some drugs, injection preparations, forms, and ARI sound timers were unavailable or damaged; Funding is relatively sufficient but early year disbursement is hampered; SOPs exist but require cluster adjustments; program activities are inconsistent (dominant passive findings, uneven breath counts, variable antibiotic duration, pre-referral is not yet uniform, use of KIA Handbooks is lacking, monitoring does not comply with guidelines); output is low (26.49%). Conclusion: Implementation is partially in accordance with the 2018 FKTP guidelines but is not yet consistent; it is recommended to strengthen active surveillance and reporting networks, standardize clinical references, uniform training for supporting units, improve logistics and critical equipment, and improve communication and monitoring to improve case detection and management compliance